OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY TO DISTINGUISH CHOROIDAL NEOVASCULARIZATION FROM MACULAR INFLAMMATORY LESIONS IN MULTIFOCAL CHOROIDITIS - Astroz, Polina; Miere, Alexandra; Mrejen, Sarah; Sekfali, Rim; Souied, Eric H; Jung, Camille; Nghiem-Buffet, Sylvia; Cohen, Salomon Y (Retina (Philadelphia, Pa.), 2018)
To characterize the macular lesions in multifocal choroiditis using multimodal imaging (MMI) and to evaluate optical coherence tomography angiography (OCTA) in distinguishing neovascular from inflammatory lesions. Retrospective review of medical records of consecutive patients diagnosed with multifocal choroiditis and macular involvement, between September 2014 and May 2016, were included. All patients underwent standard examination and MMI, including fundus color photography, fundus autofluorescence, fluorescein angiography, and spectral domain optical coherence tomography. They also underwent OCTA examination. Multimodal imaging and OCTA characteristics of inflammatory lesions and choroidal neovascularization (CNV) were compared. Eighteen eyes of 13 patients (11 females) were analyzed. The mean age was 42.9 ± 13.4 years. The lesions were first categorized as active or inactive CNV and active or inactive inflammatory lesions through conventional MMI. Using OCTA, an abnormal blood flow was observed in all active CNV (9/9) and most inactive CNV (5/6), but also in 2 of 14 lesions previously classified as active inflammatory lesions. On the contrary, no case of inactive inflammatory lesions showed abnormal blood flow. Therefore, the use of OCTA allowed a diagnosis of CNV that was not made through conventional MMI in 14% of cases of active inflammatory lesions. The combined findings of conventional imaging and OCTA demonstrate distinctive features of inflammatory lesions and CNV in multifocal choroiditis, allowing an appropriate management of these sight-threatening lesions. However, OCTA alone did not distinguish between active and inactive CNVs and should be integrated into an MMI approach.